2007
DOI: 10.1163/156856107779976105
|View full text |Cite
|
Sign up to set email alerts
|

Pressure amplification of laser induced plasma shockwaves with shock tubes for nanoparticle removal

Abstract: A method using shock tubes for amplifying the dynamic pressure of Laser Induced Plasma (LIP) shockwaves for removing sub-100-nm nanoparticles is introduced and demonstrated. The higher the amplitude of the pressure generated, the smaller the particles that can be removed and, thus the more useful for a variety of applications. Constraining the expansion of the LIP core with a shock tube is a non-contact approach to increase pressure amplitude by an order of magnitude for removal of particles without damaging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 9 publications
1
10
0
1
Order By: Relevance
“…Based on [14], a minimum diameter of D min = 59 nm PSL is calculated as the smallest particle that can be removed from Ru film (compared to 46 nm for Cr film at d cr = 2.5 mm) utilizing the LIP shockwave pressure of 93.5 kPa in air for a single laser shot without any material alterations of EUVL mask blank at critical clearance distance d cr = 3.6 mm. So it is concluded that, in order to achieve the particle removal requirement according to the ITRS 2010 update [2], pressure amplification techniques utilizing LIP, such as shock tubes [29], wet-LIP [30], and submerged shock-tubes [31], or film design approaches creating stressed films are required.…”
Section: Lip Experiments For Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on [14], a minimum diameter of D min = 59 nm PSL is calculated as the smallest particle that can be removed from Ru film (compared to 46 nm for Cr film at d cr = 2.5 mm) utilizing the LIP shockwave pressure of 93.5 kPa in air for a single laser shot without any material alterations of EUVL mask blank at critical clearance distance d cr = 3.6 mm. So it is concluded that, in order to achieve the particle removal requirement according to the ITRS 2010 update [2], pressure amplification techniques utilizing LIP, such as shock tubes [29], wet-LIP [30], and submerged shock-tubes [31], or film design approaches creating stressed films are required.…”
Section: Lip Experiments For Materialsmentioning
confidence: 99%
“…It was predicted that damage-free cleaning of 59-nm and 46-nm standard PSL particles were possible utilizing LIP shockwaves from Ru and Cr films, respectively. Removal of sub-50-nm particles from EUVL masks required utilization of LIP pressure amplification techniques [29]- [31]. It was reported that pressure amplitude can be increased from the same LIP source by using varies types of shocktubes [29].…”
Section: Conclusion and Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various techniques to remove sub-100 nm particles from solid substrates, the laser shock cleaning (LSC) process based on laser-induced breakdown (LIB) of air and plasma formation has attracted substantial attention as the process demonstrated strong potential to remove nanoscale particles from silicon wafers [5][6][7][8]. Recently, removal of polystyrene (PS) particles as small as 10 nm in diameter was reported [8]. The LSC method is not only a dry but also a non-contact technique without exposure of the surface to direct mechanical contact.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the first limitation, Dunbar et al proposed a method to enlarge the shock wave intensity using shock tubes [8]. The LIP is generated in a cylindrical tube in the proposed method, leading to propagation of a near-planar shock wave with small diffraction at the exit of the tube.…”
Section: Introductionmentioning
confidence: 99%